The Role of Slang in Digital Communication (The Peerian Journal, 2025)
In this paper, in the era of rapid digitalization, slang has become a cornerstone of modern communication. This article examines how slang evolves and thrives within the digital landscape, shaping the way individuals connect and express themselves. Texting, memes, and social media platforms act as catalysts for slang innovation, enabling rapid spreading across diverse demographics and cultural contexts. The study explores how social media amplifies linguistic creativity, with platforms like Twitter and TikTok fostering unique expressions that transcend geographical boundaries. Furthermore, it delves into the influence of memes in reinforcing and embedding slang into collective consciousness. Texting abbreviations and acronyms, such as "lol" or "brb," showcase efficiency and informality, marking a significant shift from traditional linguistic norms. The article highlights the dual role of slang in fostering inclusivity within online communities while simultaneously challenging linguistic boundaries. Through digital communication, slang not only reflects societal trends but also serves as a powerful tool for identity, humor, and community building.